Prevalence of Risk Factors for Hypertension Among Faculty at an Urban University in Uganda [Response to Letter] - Alinaitwe B; Amanya C; Muwanguzi PA; Ngabirano TD (Dove Medical Press, 2024)
Businge Alinaitwe,1 Charles Amanya,1,2 Patience A Muwanguzi,1 Tom Denis Ngabirano1 1Department of Nursing, College of Health Sciences, Makerere University, Kampala, Uganda; 2Department of Research, Hoima Regional Referral Hospital, Hoima, UgandaCorrespondence: Tom Denis Ngabirano, Department of Nursing, College of Health Sciences, Makerere University, P.O. Box 7072, Kampala, Uganda, Tel +256 772594720, Email tomngabirano@gmail.com